Soils on a warmer earth : effects of expected climate change on soil processes, with emphasis on the tropics and sub-tropics - Scharpenseel, H. W.; Schomaker, M.; Ayoub, A. (Developments in soil science ;, 1990)
The theme of this book is a far reaching one and should attract great interest, both in industrialized as well as in less developed countries. Although the question of climate change and its effects on soil productivity is overshadowed by so many current events, it is almost certain that this subject will remain on the international agenda for the years to come; not only as science and research are concerned but also in relation to development policies, agricultural policies and others, especially since poor, rich, developed and developing countries are equally threatened by these problems.